Zahid challenges Malaysians to write award-winning books - New Sabah Times English, (KK) (New Sabah Times English (KK), 2016)
KUALA LUMPUR: Datuk Seri Dr Ahmad Zahid Hamidi yesterday challenged Malaysians to write books that can draw international acclaim and even win the Nobel Prize in Literature.